2007
DOI: 10.3748/wjg.v13.i10.1547
|View full text |Cite
|
Sign up to set email alerts
|

Th immune response induced byH pylorivaccine with chitosan as adjuvant and its relation to immune protection

Abstract: AIM:To study the immunological protective effect of H pylori vaccine with chitosan as an adjuvant and its mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…In spite of the promising use of chitosan in the pharmaceutical industry, most of the chitosan researches are directed towards medical applications. For example, some studies showed that chitosan, whether it is used as an immune adjuvant, drug delivery agent or dietary fibre, could effectively promote local immune response and enhance antigen presentation (Porporatto et al, 2005;Xie et al, 2007).…”
Section: Applicationsmentioning
confidence: 99%
“…In spite of the promising use of chitosan in the pharmaceutical industry, most of the chitosan researches are directed towards medical applications. For example, some studies showed that chitosan, whether it is used as an immune adjuvant, drug delivery agent or dietary fibre, could effectively promote local immune response and enhance antigen presentation (Porporatto et al, 2005;Xie et al, 2007).…”
Section: Applicationsmentioning
confidence: 99%
“…Bivas-Benita et al immunized mice with oral Toxoplasma gondii GRA1 protein and DNA vaccineloaded chitosan particles, and successfully induced specialized anti-GRA1 IgG1 and IgG2a, indicating that it can enhance immune respons to Th1 and Th2 [21]. Xie et al revealed that H. pylori with chitosan solution as an adjuvant can protect against H. pylori infection and induce both Th1 and Th2 type immune response by oral [22]. Therefore, the type of immune response of these CS derivatives requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan solution and particles had mostly comparable effects and induced Th1 and Th2 immune responses [25]. Chitosan (88.5% DAD, Qisheng Biological Products Limited Company, China) solution was prepared in acetic acid.…”
Section: Chitosan-based Adjuvants: Comparative Preclinical Studiesmentioning
confidence: 99%